Notes On the Contributors - Institute of Creative Writing, UP-LIKHAAN (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
.